An examination of the Australian Height Datum - Filmer, Michael Shaun (Curtin University, 2010)
The Australian Height Datum (AHD) was established in 1971, and is the basis for all physical heights in Australia. However, a complete revision of the AHD has never occurred, despite problems that, although not always obvious to surveyors at the local level, have come to prominence through the introduction of Global Navigation Satellite Systems (GNSS) and gravimetric quasi/geoid models. Improvements in GNSS, quasi/geoid and sea surface topography (SSTop) models, plus moderate upgrades to the Australian Levelling Network (ANLN) since 1971 now allow a meaningful revision of the AHD to be made. This thesis first conducts an investigation of AHD/ANLN errors, culminating in the realisation of an Australian Experimental Vertical Datum (AEVD).An assessment of 1366 ANLN loops reveals 15-20 misclosures >0.5 m (up to 0.93 m), situated primarily in the interior of the continent. GNSS¡quasi/geoid information was included in a second loop-based assessment, adding redundancy in an attempt to isolate errors within the levelling sections. These assessments indicate that the ANLN database requires corrections and updating by State and Territory geodetic agencies, including the replacement of average two-way levelled height differences between benchmarks (BMs) currently in the database with forward and reverse levelled height differences. A simulation of the effects of refraction on the AHD and ANLN suggest that height errors of up to 0.4 m in central Australia may result from neglecting to apply refraction corrections to the ANLN. However, the metadata required to properly correct the ANLN for refraction is not currently available.A major objective of this thesis is to identify the causes of the north-south slope observed in the AHD when compared with geoid models. The CARS2006 climatology (oceanographic) and Rio05 combined mean dynamic topography (geodetic and oceanographic) SSTop models along with the EGM2008 and gravimetric component of AUSGeoid09 (AGQG09) SSTop estimates at tide-gauges are shown to effectively remove the north-south slope. This indicates that the north-south AHD slope was caused solely by fixing the Australian levelling survey to mean sea level (MSL) at 30 mainland tide-gauges. In addition, it was found that the vertical offset between mainland AHD and Tasmanian AHD (vertical datums separated by the sea) is negligible. The CARS2006 SSTop model provided the best estimates of SSTop at tide-gauges and was used in the final realisation of the AEVD as an SSTop correction when the AEVD is constrained to 32 AHD tide-gauges, also unifying the mainland and Tasmanian levelling networks.To determine the height system best suited to the AEVD, gravity at ANLN BMs was computed from EGM2008 and also from terrestrial gravity held in the Australian National Gravity Database (ANGD). Despite problems with both, "reconstructed" BM gravity from EGM2008 demonstrated the best results and is used for gravimetric height corrections applied to the ANLN. Differences between Helmert orthometric and normal-orthometric heights (used for the AHD) were up to 0.44 m at heights >2,000 m in the Australian Alps. However, differences between normal and normal-orthometric heights were <30 mm across most of Australia, but reached 0.17 m in the Australian Alps. Normal heights were considered most appropriate for the AEVD because of the sensitivity of Helmert orthometric heights to the poor quality of ANGD- and EGM2008- derived gravity, and normal-orthometric heights being inconsistent with quasigeoid models, particularly at elevations >1,000 m.A combined least-squares adjustment (CLSA) of the ANLN (with normal height corrections applied to the levelling) was conducted using MSL + CARS2006 at 32 AHD tide-gauges and GNSS-AGQG09 at 277 GNSS stations as weighted constraints to realise the AEVD. An outlier detection process was undertaken first, to attempt to identify the problem levelling sections of the ANLN and re-weight them so they have less infuence in the CLSA. Validation of the AEVD used GNSS-AGQG09 at 765 GNSS stations not used in the CLSA. RMS of the differences at the 765 GNSS stations between the AEVD and GNSS-AGQG09 were ±0.098 m (considered external accuracy), compared to an RMS of ±0.207 m for differences between the AHD and GNSS-AGQG09, indicating an improvement of the AEVD over the AHD.